Melting the ice eaudiobook - Burton, Jaci (Play By Play, 2014)
Everything's coming together for budding fashion designer Carolina Preston. Only months away from having her own line, she could use some publicity. That's when her brother suggests his best friend as a model—hockey player Drew Hogan. Carolina and Drew already have a history—a hot one, back in college. Unforgettable for Carolina, but for Drew, just another slap shot. This time, though, it's different. His perfect body would be for professional use only. This time, she could use him. Drew is all for it. He's looking forward to the exposure. Plus, it would give him a chance to prove to Carolina that he's changed. If only he could thaw her emotions, convince her to let down her guard and let him in just one more time . . .